Facilitating Wasteful Activities Discovery in Pure Service Environment Through Usage of Process Mining - Tomašević, Ivan; Slović, Dragoslav (International Journal of Industrial Engineering and Management, 2013)
This paper describes the possibilities of using process mining in order to facilitate the discovery of wasteful activities (in terms of lean service) in pure service organizations. The specificities of pure service systems will be analyzed, with special focus on value creation and wasteful activities in service organizations. Existing process mining algorithms can be applied to event logs (cases that have been completed, i.e. “post-mortem” cases) created by Enterprise Systems in order to discover wasteful activities and flow interruptions. Process mining application can also be extended to operational support of lean transformation (partial cases), in order to analyze cases that have not yet been completed (“pre-mortem” cases) and predict the appearance of wasteful activities and to recommend suitable actions for minimizing possible wastes. Article history: Received (05.11.2012); Revised (03.05.2013); Accepted (20.05.2013)